Validation of a wireless shoe insole for ground reaction force measurement - Burns, G. T.; Deneweth Zendler, J.; Zernicke, R. F. (Journal of Sports Sciences, 2019)
Ground reaction force measurements are a fundamental element of kinetic analyses of locomotion, yet they are traditionally constrained to laboratory settings or stationary frames. This study assessed the validity and reliability of a new wireless in-shoe system (Novel Loadsol/Pedoped) for field-based ground reaction force measurement in hopping, walking, and running. Twenty participants bilaterally hopped on a force plate and walked (5 km/hr) and ran (10 km/hr) on an instrumented treadmill on two separate days while wearing the insoles. GRFs were recorded simultaneously on each respective system. Peak GRF in hopping and peak GRF, contact time (CT), and impulse (IMP) in walking and running were compared on a per-hop and step-by-step basis. In hopping, the insoles demonstrated excellent agreement with the force plate (ICC: 0.96). In walking and running, the insoles demonstrated good-to-excellent agreement with the treadmill across all measures (ICCs: 0.88-0.96) and were reliable across sessions (ICCs within 0.00-0.03). A separate verification study with ten participants was conducted to assess a correction algorithm for further agreement improvement but demonstrated little meaningful change in systemic agreements. These results indicated that the Novel Loadsol system is a valid and reliable tool for wireless ground reaction force measurement in hopping, walking, and running.